PROFIL KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR KELAS TINGGI DI MALUMBI KABUPATEN SUMBA TIMUR - Iona Lisa Ndakularak; Erwin Randjawali; Mayun Erawati Nggaba; Stevvileny Angu Bima; Yuliana Tamu Ina; Djemi Djami Ishak; Yeni Rinawati (Program Studi PGSD Universitas Flores, 2023)
This study aims to describe the numeracy ability profile of high school elementary school students in Malumbi, East Sumba Regency. This numeracy ability was carried out at a grade 5 school in the high class area as a reference point used to analyze comparisons before finally moving on to a larger stage of research scope. This type of research is qualitative with the instrument used in data collection is the Numeral Test, namely the test uses EGMA (Early Grade Mathematics Assessment) measurements, interviews and observations. The results of the research on the school's numeracy skills which were collected through the numeration test found that elementary school students were in the low category with an average score of 18.43. This is caused by several factors such as textbooks which so far have only been provided while at school, learning media that are less interesting so learning becomes boring, and students are not used to being given story questions, so that students' numeracy skills in solving number pattern problems, recognizing and comparing numbers and there are still many mistakes in word problems, as well as follow-up on teacher competence in teaching mathematics so that there are no misconceptions in learning.